Public Swearing In Ceremony for Judges Charles Hamlin, Gene Gomes, Ralph Nunez, Mario Olmos and Victor Papadakis at Veterans' Memorial Auditorium - Watkins, Howard::::::::: (1983)
Justice George Zenovich administering oath to Victor Papadakis with wife Kathy Papadakis holding judicial robe